2014
DOI: 10.3390/ijerph110303233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ampicillin, Streptomycin, Penicillin and Tetracycline on Metal Resistant and Non-Resistant Staphylococcus aureus

Abstract: There is an arising and concerning issue in the field of bacterial resistance, which is confirmed by the number of deaths associated with drug-resistant bacterial infections. The aim of this study was to compare the effects of antibiotics on Staphylococcus aureus non-resistant strain and strains resistant to cadmium or lead ions. Metal resistant strains were created by the gradual addition of 2 mM solution of metal ions (cadmium or lead) to the S. aureus culture. An increasing antimicrobial effect of ampicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 64 publications
4
39
0
1
Order By: Relevance
“…The strains of the bacterium were stored as a spore suspension in 20% ( v/v ) glycerol at −20°C according to the conditions mentioned in Chudobova et al [36, 37]. Prior to use in this study, the strains were thawed and the glycerol was removed by washing with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…The strains of the bacterium were stored as a spore suspension in 20% ( v/v ) glycerol at −20°C according to the conditions mentioned in Chudobova et al [36, 37]. Prior to use in this study, the strains were thawed and the glycerol was removed by washing with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of biological properties, the effect of UV radiation (laboratory and stratospheric) on the resistance of bacterial strains to environmental externalities, such as conventional antibiotic drugs or their alternative as selenium nanoparticles [24,25], was further monitored. It was shown that the exposure of UV significantly weakened the resistance of bacteria, and the application of antibiotic drugs or nanoparticles became more effective.…”
Section: Resistancementioning
confidence: 99%
“…Agricultural practices have contributed as a major source of heavy metals and antibiotics in contamination of water and soils (Zhu et al 2013). Moreover, metal ions accumulated to critical concentration levels in the environment promote the development of bacterial resistance to other xenobiotics, including antibiotics, which may impact public health (Seiler and Berendonk 2012;Chudobova et al 2014). Therefore, the co-selections of c Fig.…”
Section: Effects Of Zn Concentration and Binary Exposure On Bacterialmentioning
confidence: 98%
“…More and more bacterial strains have been found to be resistant to both heavy metals and antibiotics in different niches, including petroleum hydrocarbon contaminated soils (Máthé et al 2012), agricultural soils , surface water (Koc et al 2013), mangrove (Zhang et al 2012a;Pan et al 2010) and even Antarctic shallow sediments (Giudice et al 2013). Heavy metals have been established as one of the antibiotic resistance determinants (Martinez 2009;Chudobova et al 2014). Moreover, bacteria may pose threat to human and ecological health (Martinez 2008;Hazen et al 2010) once antibiotic resistance genes are acquired by environmental isolates including pathogens through gene transfer , which deserves more attention in both research and management.…”
Section: Introductionmentioning
confidence: 99%